Wealth, credit conditions and consumption: evidence from South Africa - Aron, J; Muellbauer, J (University of Oxford, 2011)
There is widespread disagreement about the role of housing wealth in explaining consumption. This paper exploits liquid and illiquid wealth time series from household balance sheet data for South Africa, previously constructed by the authors, to explain fluctuations in the ratios of consumption and household debt to income in South Africa, from 1971 to 2005. The paper emphasizes the role of substantial credit liberalization and of wealth, treating credit conditions as a latent variable with key interactions with drivers of consumption and debt. Credit conditions are proxied by a spline function entering jointly estimated consumption, debt and income expectations equations in a 'latent interactive variable equation system' (LIVES). The empirical results corroborate the theory in the paper, confirming that consumption relative to income is driven by credit liberalization, fluctuations in a range of asset values and asset accumulation, uncertainty and income expectations, inter alia. The paper confirms a collateral interpretation of housing wealth on consumption as opposed to a life-cycle interpretation. The paper also throws important light on the monetary policy transmission mechanism in South Africa.